A imaginária processional na Semana Santa em Minas Gerais: estudo realizado nas cidades de Santa Bárbara, Catas Altas, Santa Luzia e Sabará - Maria Regina Emery Quites (1997)
This dissertation report on the processional images from Minas Gerais region, particularly from the important religious traditions of Holy Week in Santa Bárbara, Catas Altas, Santa Luzia e Sabará. The images selected for study are Our Lady of Sorrows, Dead Crist and “Senhor dos Passos” ( Christ on the knee carrying the cross), which are the central iconographical images of Holly Week. The images are classified, based on their method of construction, into the following categories: Articulated images, de Vestir ( dressed images ) and Roca images. We note one increase level of simplification of articulated images for roca images. These articulations permit the images to be moved into different positions and to be dressed.The articulations were classified into five model types: male/female sphere; male/ female simple; solid sphere; sphere in two halves and hinges. The importance of these images is indisputable, having been used since the eighteenth century to the present day during the Holly Week. These work of art are of great value when their role in popular religious and social functions is considered together with their high technical, stylistic quality. Their use in religious processions and plays is found to be similar in each of the cities studied.